(untitled) (Journal of Economics and Management Research, 2021)
هدفت هذه الدراسة إلى التعرف على نظام الملاءة الجزائري لشركات التأمين وتطورات نظام الملاءة الأوروبي من نظام الملاءة 1 إلى نظام الملاءة 2 والمقارنة بينها، ثم استخلاص أهم الفروقات وأوجه التشابه بين أنظمة الملاءة الثلاث. وقد توصلت الدراسة إلى أن نظام الملاءة الجزائري لم يواكب تطورات أنظمة الملاءة الأوروبية لاختلافه مع نظام الملاءة 2 في المتطلبات النوعية، وتوافقه مع نظام الملاءة 1 في الارتكاز على المتطلبات الكمية، والنسب الثابتة في تحديد هامش الملاءة، وعدم المرونة في استثمار أموال شركات التأمين. This study aims to identify the Algerian solvency system for insurance companies and the developments of the European solvency system from the solvency 1 to the solvency 2 and compare them. Then extract the most important differences and similarities between the three solvency systems. The study concluded that the Algerian solvency system did not keep pace with the developments of European solvency systems, because it differed with the solvency system 2 in qualitative requirements. And it is similar with the solvency system 1 in basing on quantitative requirements, fixed ratios in determining the solvency margin, and inflexibility in the investments of insurance companies.